Deferral of Leaf Senescence with Calcium - Poovaiah, B. W. (1973)
In view of the possibility that senescence may be a consequence of the deterioration of membrane compartments in the cells of leaves, calcium was studied as a possible agent which might defer senescence. The senescence of corn leaf discs was deferred by added calcium, and the effect was additive to the cytokinin deferral of senescence. Likewise, the senescence of Rumex leaf discs was deferred by added calcium, and the effect was additive to the gibberellin deferral of senescence. Detailed experiments with corn leaf discs established that the increase in apparent free space associated with senescence was completely prevented by calcium. An increase in hydraulic permeability during senescence was likewise demonstrated, and this increase was deferred by calcium; calcium plus benzyladenine was even more effective. Each of the measured functions of leaf senescence (chlorophyll content, protein decrease, apparent free space increase, and hydraulic permeability increase) was suppressed by calcium, and the interpretation is offered that the effects are a consequence of the calcium function in maintaining cellular membranes.